Development of the Self-care Module of Assertif Communication Theory to Reduce Toxic Behavior - Ningsih, Aprilia Sulistia; Isriyah, Mudafiatun; Fauziyah, Nailul (Konseling Edukasi : Journal of Guidance and Counseling, 2024)
Development of the Self-Care Module Of Assertive Communnication Theory to Reduce Toxic Behavior. The guidance and counseling services provided so far have not paid attention to the problems and the services provided to overcome these problems, especially toxic behavior. This research was conducted to adjust between the problems and counseling guidance services needed so that the services provided are effective in overcoming the problem, as well as to determine the need for guidance service modules and the concept of self-care counseling with assertive communication theory to reduce toxic behavior. The research was conducted using Research and Development (R&D) method with ADDIE model. The results of this study show the need for the development of the Iself care concept module with assertive communication theory to reduce toxic behavior is needed, and this self-care concept module can be developed through limited scale or small group tests, material validation tests, language validation tests and practical validation tests, so that this module can be used as a reference for providing counseling guidance services, especially to reduce toxic behavior.Keywords: Self Care, Assertive Communication, Module